Is there a role for an active fiscal stabilization policy? - Torben M. Andersen (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper discusses the need and scope for an active fiscal stabilization policy. It is argued that the effectiveness of fiscal policy as a short run stabilizer does not depend on the long run multipliers of (balanced budget) fiscal policies. To the extent that activity can be affected by aggregate demand in the short run, there is a case for a fiscal stabilization policy in terms of temporary variations in taxes or public consumption contingent on the state of the economy. The effectiveness of fiscal policy is supported by empirical evidence. However, an appropriate policy intervention depends both on the nature of the shock and the structure of the economy. There are thus fundamental information problems in pursuing discretionary fiscal policies on top of political economy concerns, and fiscal fine-tuning is not to be recommended. Automatic stabilizers do not to the same extent suffer from these problems, but their strength is not by design but the net result of other policy considerations. Hence, there is a need to consider the structure and size of automatic stabilizers.
Keywords: E6; 330; shocks; insurance; adjustment failures; rules; discretion and fiscal policy; Antizyklische Finanzpolitik; Finanzpolitik; Konjunkturpolitik; Diskretionäre Politik; Eingebauter Stabilisator; Regelgebundene Politik